Associations of bird and bat species richness with temperature and remote sensing‐based vegetation structure on a tropical mountain. (5th December 2021) - Vogeler, Anna‐Valeska Bettina; Otte, Insa; Ferger, Stefan; Helbig‐Bonitz, Maria; Hemp, Andreas; Nauss, Thomas; Böhning‐Gaese, Katrin; Schleuning, Matthias; Tschapka, Marco; Albrecht, Jörg
Abstract: Given the current challenges of global change, e.g., through increasing temperatures and changes in habitat quality, it is essential to gain a better understanding of how species are linked to the conditions of their environment. Bats and birds fulfill crucial ecosystem functions as highly mobile long‐distance seed dispersers, pollinators, and insect predators and might be influenced not only by abiotic conditions such as temperature, but also by structural parameters of their habitats. We hypothesized that mean annual temperature and vegetation structures are key determinants of flying vertebrate species richness along the slopes of Mt. Kilimanjaro, Tanzania. We used Light Detection and Ranging (LiDAR) to characterize the three‐dimensional habitat structure across different forest strata and recorded mean annual temperature on 58 study sites along the elevational gradient of Mt. Kilimanjaro. Our results show that both bat and bird species richness were significantly associated with temperature and a LiDAR derived measure of canopy density. In combination, temperature and LiDAR‐derived vegetation structure described over 90% of the variability in bat and bird species richness along the elevational gradient. Our findings reveal that climate data and measures of canopy structure obtained by remote sensing can be used to approximate the richness of flying vertebrates on tropical mountains and are highly suitable monitoring tools in conservation programs for these functionally important taxa. Abstract : Given the current challenges of global change, e.g., through increasing temperatures and changes in habitat quality, it is essential to gain a better understanding of how species are linked to the conditions of their environment. Bats and birds fulfil crucial ecosystem functions as highly mobile long‐distance seed dispersers, pollinators and insect predators and might be influenced not only by abiotic conditions such as temperature, but also by structural parameters of their habitats. Our results show that both bat and bird species richness were significantly associated with temperature and a LiDAR derived measure of canopy density.